Understanding art : a guide for teachers - Wenham, Martin (London [etc.] SAGE, 2003)
Martin Wenham explores the basic knowledge that children need to know in order to explore and experiment with the visual language that artists use to communicate. The National Curriculum places a strong emphasis on experimenting with and applying the visual elements.
Incluye referencias bibliográficas (p. 160-161) e índice
Keywords: Arte -- Estudio y enseñanza; Didáctica